Tourism and terrorism : a hotel industry perspective / Joan C. Henderson...[et al.] - Henderson, Joan C.; Shufen, Chew; Huifen, Lee; Xiang, Lee Ling (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2010)
The paper examines the consequences of terrorism for tourism with particular reference to the hotel industry and the case of Singapore. Terrorist activity is shown to have adverse impacts for destinations where it occurs and hotels to be attractive targets for attacks. The risks are recognised and management is attempting to secure properties against damage. Such a task can be daunting and is illustrated by a discussion of circumstances in Singapore based on information collected from hotel security managers and other experts there. There is a need for constant vigilance. Tools to combat terrorism directed at hotels are both technological and human and internal and external communications, cooperation and collaboration have an important part to play in effective resistance.